AB1155 WORK DISABILITY AND PREDICTORS OF POOR WORK OUTCOME IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS. (2nd June 2020) - Durak Ediboglu, E.; Solmaz, D.; Oz, H. E.; Kabadayi, G.; Cinakli, H.; Otman Akad, E.; Ozmen, M.; Akar, S.
Abstract : Background: Axial spondyloarthritis (axSpA) is a chronic inflammatory disease which may lead substantial functional limitation. The disease more commonly affects men in their third decade of life. For patients with chronic disease participation in paid work may be the result of series factors like disease severity, effectiveness of the health care, availability and the type of work. Previously it was reported that ankylosing spondylitis may cause adverse work outcome. Objectives: To understand the impact of axSpA on work disability and the factors associated with poor work outcome. Methods: A cross-sectional survey was performed among323 patients withaxSpA according to ASAS classification criteriafrom one tertiary center. In total 219 (67.8%) patients were working age at the time study. The others were student, housewife or retired. Demographic, social and disease related characteristics were collected. Characteristic that might be associated with premature work loss were evaluated byunivariable and multivariable logistic regression analysis. Results: Out of 219 axSpA patients (155 [71%] r-axSpA and 64 nr-axSpA, 69% HLA-B27 positive) who have a work at least once 47 (22%) was either withdrawn from work (n=35) or retired due to disability (n=12) during median (IQR) 12 (12) years symptom duration. Demographic and disease related characteristics of the patients with or without work diasbilitywere summarized in the table. In univariate analysis gender, smoking, education levels, the presence of peripheral arthritis, BASMI score and radiographically presence of syndesmophyte and hip involvement were found to be associated with poor work outcome. However poor work outcome were similar between r- and nr-axSpA patients. In regression analysis low education level (HR:3.4 [95%CI:1.4-8.6], P=0.007), peripheral arthritis (HR:2.7[95%CI:1.07-6.8], P=0.035), and ever smoking (HR:4.9 [95%CI:1.3-18.0], P=0.02) were independent predictors of work disability. Conclusion: Our results suggest that there is still remarkable poor work outcome among axSpA patients and work disability might be similar in r- and nr-axSpA. Patients who are smoker, with low education levels, and peripheral arthritis seem to be at risk for premature work loss. Disclosure of Interests: None declared